2012
DOI: 10.1176/appi.ajp.2012.11081245
|View full text |Cite
|
Sign up to set email alerts
|

Differing Amygdala Responses to Facial Expressions in Children and Adults With Bipolar Disorder

Abstract: Objective Bipolar disorder (BD) is highly debilitating in both children and adults. Child and adult BD patients show both behavioral deficits in face emotion processing and abnormal amygdala activation. However, amygdala function in pediatric vs. adult BD patients has never been compared directly. Method This study compared amygdala responses to emotional facial expressions in 74 subjects [pediatric (N=18) and adult (N=17) patients with BD, healthy volunteer (HV) children (N=15) and adults (N=22)]. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 39 publications
7
46
1
Order By: Relevance
“…Further, the ILF connects the ventrolateral prefrontal cortex to the occipitotemporal cortices and, pertinent to BD, connects cortical areas involved with the recognition and social emotional processing of faces (Schmahmann and Pandya, 2006). Previous fMRI studies in youth with BD have shown temporal hyperactivation in the amygdala to particular facial expressions when compared to HCs (Kalmar et al, 2009; Kim et al, 2012). The IFOF connects visual and auditory association cortices with the prefrontal cortex and intermingles with the UF (Schmahmann and Pandya, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Further, the ILF connects the ventrolateral prefrontal cortex to the occipitotemporal cortices and, pertinent to BD, connects cortical areas involved with the recognition and social emotional processing of faces (Schmahmann and Pandya, 2006). Previous fMRI studies in youth with BD have shown temporal hyperactivation in the amygdala to particular facial expressions when compared to HCs (Kalmar et al, 2009; Kim et al, 2012). The IFOF connects visual and auditory association cortices with the prefrontal cortex and intermingles with the UF (Schmahmann and Pandya, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Functional neuroimaging techniques have revealed consistent findings with the structural neuroimaging studies. Thus, abnormal amygdala activation during face processing appears to be more pervasive in children and adolescents than in adults with bipolar disorder (27), and neurobiological changes in activation patterns involving fronto-limbic circuitry have been reported in relation to different illness phase and mood states. The difficulties to deactivate the default mode network is another consistent finding across mood states (28,29), but might be very unspecific.…”
Section: Genetics and Neuroimagingmentioning
confidence: 99%
“…To our knowledge, only four currently-published task-related functional magnetic resonance imaging (fMRI) studies have directly compared BD-youths and BD-adults in the same study 1619 . Specifically, Kim (2012) found that BD-youths had greater amygdala activation during emotional face recognition than BD-adults 16 .…”
Section: Introductionmentioning
confidence: 99%